2016
DOI: 10.1177/1942775116640254
|View full text |Cite
|
Sign up to set email alerts
|

Investigating How to Support Principals as Instructional Leaders in Mathematics

Abstract: We present a framework for considering principals' knowledge and actions to support high-quality instruction in a specific content area (mathematics). Using design research, we engaged principals in professional development and assessed principals' ability to identify aspects of high-quality mathematical tasks and instruction through pre-post task sort analyses and classroom video analyses. Significant differences occurred in principals' identification of high-quality mathematics tasks and instruction, student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…A study examining quality and efficacy of professional development found that district facilitators initially struggled to provide learning opportunities for teachers to engage with conceptual ideas, instead focusing on the forms of the reform. Over 4 years, with expert support, the facilitators improved their adult learning practices and led professional development sessions in ways that allowed teachers to engage deeply with the conceptual ideas in teaching and learning ambitious mathematics (Boston et al, 2016). Administrators as a lever of support, then, are situated in the imperfect and often messy process of instructional improvement.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study examining quality and efficacy of professional development found that district facilitators initially struggled to provide learning opportunities for teachers to engage with conceptual ideas, instead focusing on the forms of the reform. Over 4 years, with expert support, the facilitators improved their adult learning practices and led professional development sessions in ways that allowed teachers to engage deeply with the conceptual ideas in teaching and learning ambitious mathematics (Boston et al, 2016). Administrators as a lever of support, then, are situated in the imperfect and often messy process of instructional improvement.…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…In each of the four districts, principals (and sometimes assistant principals) attended district-sponsored professional development sessions on both high-quality mathematics instruction (sometimes with their teachers or math coaches), as well as on observation and feedback routines. While the research is scant, there is evidence that school leaders can learn content-specific leadership practices through professional development (Barth, 1986; Boston, Henrick, Gibbons, Berebitsky, & Colby, 2016; Carver, Steele, & Herbel-Eisenmann, 2010; Nelson, 1997; Sassi & Nelson, 1999). Given these districts’ ambitious goals for instructional improvement and infrastructures of support (discussed in detail below), they presented promising sites for exploring how administrators might work as part of a coherent instructional system to support teachers’ development of ambitious practice (Cobb & Jackson, 2011a).…”
Section: Data Sources and Methodsmentioning
confidence: 99%
“…Coaches, like all other adults, benefit from professional development to improve their practice (Gallucci, Van Lare, Yoon, & Boatright, 2010). Similar to extant research on supports for principals as instructional leaders (Boston, Henrick, Gibbons, Berebitsky, & Colby, 2016), coaches would benefit from formal and informal supervision and professional learning so they can carry out leadership actions in a manner that advances district and school goals.…”
Section: Challenges To Transforming Coachingmentioning
confidence: 99%
“…Teachers instruct and impart knowledge to others. They have great responsibilities in the education field (Boston, Henrick, Gibbons, Berebitsky, & Colby, 2017). They are the beings who transform the pupils into positive human beings.…”
Section: Literature Reviewmentioning
confidence: 99%